STANDARDIZATION OF NEIKURI (OIL DROP TEST OF URINE) - A SIDDHA DIAGNOSTIC METHOD - dharshini, K. Vidya; Victoria, S.; Krishnaven, M (International Journal of Ayurveda and Pharma Research, 2018)
Neikuri is an antique method of urine examination, based on distribution of oil drop in urine which is a remarkable diagnostic and prognostic tool in Siddha system of medicine. Even though these diagnostic method not commonly used in clinical practice and elaborate scientific studies of Neikuri are lacking. Aim: The aim of the study was to test the protocols of the examination of Neikuri for the standardization. Materials and methods: 100 patients were selected and studied with twelve parameters to test the Neikuri. Correlation was considered between the reading of Neikuri and Naadi. Results: Based on the observation, the urine needs to place in a circular glass utensil (3.5 inch petri dish preferable) and a drop (0.25 – 0.5?L) of sesame oil derived from black sesame seeds need to placed less than 2mm height from the surface of the urine, in day time to test the Neikuri. Further the test needs to perform within one and a half an hour from the collection of urine. Conclusion: In conclusion we suggest the methods could be used as a standard protocol for testing Neikuri.